Satisfacción del usuario de los servicios de consulta externa de pediatría del Hospital Guillermo Almenara Irigoyen, Lima, Perú, 2007 - Tito Hermitaño, Magdieli (2019)
Objective: To determine the users’ satisfaction degree in the outpatient Pediatric Services at the Guillermo AlmenaraIrigoyen General Hospital and identify possible improvements. Methodology: This is a cross-sectional descriptivestudy, for which it was used a satisfaction questionnaire that was administered to mothers who came looking for healthcare for their children in the pediatric outpatient clinic during the first week of July 2007. The sample consisted of 184mothers in a population of 355. Results: From the 184 mothers surveyed who visited the pediatric clinic 69% knew thedoctor’s name and 47% knew the nurse’s name. 75% said that service time is right, 87% indicated that the staff wasfriendly and 83% said that most of the time the staff showed interest in helping them. As for the physical conditions ofthe facilities, an average of more than 70% of mothers perceived that it was as they had expected. In the numerical scalefrom 1 to 10 in which the patient had to rate the recommendation for this service, 66.3% marked 7 and 8. Conclusions:In general pediatrics service is recommended from the standpoint of the satisfaction experience of mothers surveyedin an average score of 7 on a scale from 0 to 10. The recommendation would be to improve the time in the waitingprocess, prompt attention and optimize the friendliness in the whole process of care.